Behavioral and Neural Responses to Tone Errors in Foreign‐Accented Mandarin. Issue 2 (21st October 2020) - Pelzl, Eric; Lau, Ellen F.; Jackson, Scott R.; Guo, Taomei; Gor, Kira
Abstract: Previous event‐related potentials (ERP) research has investigated how foreign accent modulates listeners' neural responses to lexical‐semantic and morphosyntactic errors. We extended this line of research to consider whether pronunciation errors in Mandarin Chinese are processed differently when a foreign‐accented speaker makes them relative to when a native‐accented speaker makes them (a conceptual replication using the materials from Pelzl et al., 2019). We evaluated behavioral judgments, the N400, and late positive component while native speakers listened to native and foreign‐accented sentences containing tone and rhyme pronunciation errors. We observed effects that suggested that the participants were prone to detect errors in foreign‐accented speech more often in sentences with no critical word deviation but also were less likely to reject critical tone errors produced by the foreign‐accented speaker. ERP results showed a main effect of accent on late positive components that suggested a difference in degree for sensitivity to foreign‐accented compared to native‐accented pronunciation errors rather than a completely different response pattern. We found no effect of accent on N400s, with statistically significant differences between tone and rhyme errors regardless of speaker accent. Abstract :